2010
DOI: 10.1007/s11113-010-9175-0
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Health Care Seeking Behavior in a Post-Conflict HIPC: The Case of Rwanda

Abstract: Rwanda, Maternal health, Place of delivery, Conflict,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…Also, impoverishment, misery, and early marriage are the consequences of warfare, which stimulates maternal mortality (Kottegoda et al, 2008). In addition, in most conflicts, the parties of war cut off all resources, block the ways of delivering health care and medical equipment to war-torn regions, and ban the mobility of emergency vehicles; the pregnant mothers could hardly have access to maternity care (Mullany et al,2008;Chandrasekhar et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, impoverishment, misery, and early marriage are the consequences of warfare, which stimulates maternal mortality (Kottegoda et al, 2008). In addition, in most conflicts, the parties of war cut off all resources, block the ways of delivering health care and medical equipment to war-torn regions, and ban the mobility of emergency vehicles; the pregnant mothers could hardly have access to maternity care (Mullany et al,2008;Chandrasekhar et al, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Several studies (Amin et al, 2010; Chandrasekhar et al, 2011; Karim et al, 2010; Osubor et al, 2006) associate the high MMR to the widespread practice of home birth without skilled birth attendants. These studies analyzed the geographic, socioeconomic, and contextual factors impacting the utilization of maternal health services.…”
Section: Maternal Mortality In Ethiopia: a Brief Backgroundmentioning
confidence: 99%
“…These studies analyzed the geographic, socioeconomic, and contextual factors impacting the utilization of maternal health services. Among these factors, women’s autonomy (Woldemicael & Tenkorang, 2010), household income (Amin et al, 2010; Chandrasekhar et al, 2011), distance from health facilities and transportation (Karim et al, 2010; Okojie, 1994), residence in rural versus urban settings (Nigussie et al, 2004), cost of maternal health services (Osubor et al, 2006), and access to radio (Karim et al, 2010) appeared to have the largest impact. Woldemicael and Tenkorang (2010) measured women’s autonomy using women’s freedom of mobility, control over household resources, ability to make decisions on household purchases, freedom from domestic violence, and participation in child-related decisions.…”
Section: Maternal Mortality In Ethiopia: a Brief Backgroundmentioning
confidence: 99%
“…High MMRs were also reported in parts of Burma, where the military junta had attempted to cut off all resources, and alternative ways of delivering health care had to be sought (Mullany et al 2008 ). Chandrasekhar et al ( 2011 ) showed that the conflict in Rwanda led to a decrease in the number of births given in a health facility. Some populations affected by conflict may, on the other hand, experience an improvement in health.…”
Section: Conflict Health and Gender: Literature Reviewmentioning
confidence: 99%